Sodium+/taurocholate cotransporting polypeptide as target therapy for liver fibrosis. Issue 7 (15th July 2021) - Salhab, Ahmad; Amer, Johnny; Lu, Yinying; Safadi, Rifaat
Abstract : Objective: Sodium + / taurocholate cotransporting polypeptide (NTCP) is a membrane transporter affecting the enterohepatic circulation of bile acids (BAs). We aimed to evaluate NTCP's roles in humans and animal models of liver fibrosis (LF). Design: Primary hepatic stellate cells (pHSCs) isolated from livers biopsies of patients with LF with different fibrosis grading were stained for NTCP. NTCP gene silencing, taurocholic acid (TCA), obeticholic acid (OCA), epigallocatechin gallate (EGCG) and HA-100 dihydrochloride (HA-100) were used as tools to modulate NTCP expression on human HSC line (LX2). BA trafficking/uptake were assessed extracellularly (LX2 culture medium) and intracellularly following treatment with/without NTCP neutralizing antibody. LF models of C57/BL6 mice of carbon tetrachloride (CCl4 ) and leptin-deficient ( Ob/Ob ) fed with high-fat diet ( Ob/Ob HFD ) were evaluated for pHSCs-NTCP expressions, metabolic and LF profiles following intraperitoneal injections of NTCP neutralizing antibody. Results: pHSCs from F3/F4-scored patients of LF exhibit threefold increased NTCP expressions compared with F0-scored patients (p<0.0001). Sorted-activated HSCs (LX2 αSMA+ ) showed high expressions of NTCP and high TCA uptake in vitro and triggered a further increase in their activations. This phenomenon was inhibited with NTCP small interfering RNA and the NTCP neutralizing antibody. Sorted LX2 NTCP+ (high alpha smooth muscle actin (αSMA)/high NTCP) cells showed high phosphorylated pathways of AKT/mTOR and protein kinase C (PKC) accompanied with a decrease in farnesoid X receptor expression. Moreover, LX2 NTCP+ cells treated with EGCG, OCA and PKC inhibitor HA-100 significantly decreased NTCP and αSMA. NTCP neutralizing antibody inhibited NTCP (less TCA uptake); it attenuated LF in both CCl4 and Ob/Ob HFD animal models with ameliorated metabolic profile. Conclusion: NTCP expression is linearly correlated with fibrosis severity. Modulated BA trafficking could be an important step in LF pathogenesis. Antagonising BA uptake may suggest a therapeutic strategy for preventing disease progression.